Desenvolvimento de materiais bioativos para obliteração de túbulos dentinários no tratamento de hipersensibilidade dentinária - SALDANHA, Luanna Marinho Sereno Nery (2024)
Interest in developing materials for the treatment of dentin hypersensitivity has been growing over the years. Dentin hypersensitivity (DH) is one of the most common diseases in current clinical practice; defined as pain resulting from exposure of dentin in response to chemical, thermal, tactile or osmotic stimuli. HD has gained prominence due to its increasing prevalence, becoming a constant concern for patients. The objective of this work was to propose the development of bioactive desensitizing agents for the treatment of dentin hypersensitivity. In chapter 1, the development of experimental pastes with different concentrations of ammonium niobium oxalate (5,10,20%), compared to commercial desensitizers, divided between 5 treatment groups (n=5) was proposed. The assessment of the potential for obliteration of the tubules was done through the dentin permeability test, carried out immediately after applying the pastes, 7, 14 and 21 days later. Between readings, the pastes were reapplied and the samples remained stored in a phosphate-buffered saline (PBS) solution, changed every 7 days. At the end of the evaluation period, scanning electron microscopy (SEM) images were taken to analyze the surfaces, in addition to evaluating cytotoxicity. Thus, the experimental pastes regardless of concentration showed a large reduction in permeability from the immediate period; while commercial pastes showed a greater reduction after 7 days of the first application. SEM images showed the formation of a thick layer composed of precipitates of the material and successive application of the pastes, for all experimental groups. Therefore, it is concluded that niobium oxalate pastes are capable of considerably reducing dentin permeability in the short and long term, regardless of the concentration applied. In chapter 2, the development of a suspension containing bioactive glass particles (45S5) and glutaraldehyde was proposed, comparing it with two control solutions, commercial and experimental. They are also evaluated by the dentin permeability test and SEM analysis. The experimental group with the addition of bioglass presented lower permeability values in the immediate analysis compared to the control, commercial and experimental groups. Lp values for this period showed statistically significant differences for all groups. But at the end of the study there was no statistical difference between the different treatments (p > 0.05). Therefore, we can conclude that the experimental suspension containing 45S5 bioglass had better performance in the immediate term, but during the study it proved to be similar to the control solutions. These findings allow the emergence of new treatments for dentin hypersensitivity.